Reporting abuse in sport: a question of power?. Issue 3 (3rd July 2019) - Solstad, Gerd Marie
Abstract: Although sexual abuse occurs within sport, few athletes formally report it while they are still active participants. At the same time, formal reporting channels in sport often constitute a central part of sport organisations' safeguarding frameworks. Therefore, how reporting procedures are perceived and made sense of by athletes and others in sport is important for understanding their potential as well as their limitations. The article addresses this question through a sociological lens inspired by Steven Lukes and Norbert Elias that foregrounds power and social belonging. Sport leaders, coaches and (women) athletes from organised sport in Zambia were interviewed about their perspectives on the prospect of reporting abuse through formal channels in sport. Issues perceived as reporting barriers included fears related to punishment, not being believed, being gossiped about, and being excluded from sport. Reporting sexual abuse was construed as a task that potentially jeopardised athletes' social position as well as their sport privileges and remaining silent or telling a trusted friend about abuse was articulated as the safest alternative. The uncertainty associated with the reporting process is discussed in relation to decision-making, agenda-setting, and ideological power and the social meanings ascribed to sport participation. I conclude that the role of power and social belonging should be considered central aspects of the reporting conundrum, and that these dimensions deserve due attention within safeguarding in sport.